Bone Response to Osteopontin-Functionalized Carboxyethylphosphonic Acid-Modified Implants. Experimental Study in a Minipig Model - Aragoneses, Javier; López-Valverde, Nansi; López-Valverde, Antonio; Rodríguez, Cinthia; Macedo De Sousa, Bruno; Aragoneses, Juan Manuel (Frontiers in Materials, 2022)
Currently, dental implants have become a common and reliable treatment for restoring masticatory function in edentulous patients. Their surface topography is of great importance for the adhesion and remodeling of bone cells, both in the initial phases and over time, and different strategies have been proposed to improve the biological performance of conventional sandblasted, large-grit, acid-etched implant surfaces. Corrosion has been identified as one of the causes of implant failure due to contact with oral fluids. Carboxyethylphosphonic acid is a potent anticorrosive that would form stable bonds with titanium oxide, generating an organic layer on which modifications could be made to improve cell adhesion. Osteopontin is considered a molecule capable of improving the osseointegration of titanium. Our study evaluated the osseointegration capacity of titanium implants modified with carboxyethylphosphonic acid and functionalized with osteopontin in a minipig model. A total of 16 implants were inserted in the tibial diaphysis of two minipigs, 8 implants modified with carboxyethylphosphonic acid and functionalized with osteopontin from the experimental group and 8 from the control group with sandblasted, large-grit, acid-etched surface treatment. After 4 weeks, the animals were sacrificed and the samples were analyzed by histomorphometric analysis, assessing bone-implant contact, cortical bone-implant contact, percentage of new bone, peri-implant bone density and interthread bone area interthread. Statistical analysis was performed using SPSS v.18. Statistical significance was found between groups for the percentage of new bone (p=0.04) and for interthread bone area interthread (p=0.01). Functionalization of titanium surfaces by osteopontin may be of interest for conditioning bone remodeling in the early stages of osseointegration, although in vivo studies are needed to determine its real influence in this aspect.